1999
DOI: 10.1007/s004670050596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound and dimercaptosuccinic acid scintigraphy changes in acute pyelonephritis

Abstract: The strategy for morphological investigations in children with acute pyelonephritis (APN) remains debatable. We studied 70 children (median age 2.0 years) admitted with a first episode of pyelonephritis using a high-resolution ultrasound technique (RUS) and compared the results with 99m technetium-dimercaptosuccinic acid (DMSA) renal scintigraphy. The DMSA scan was abnormal in 62 children (89%). However, using a high-frequency transducer we found abnormal sonogram changes in 61 children (87%), consisting of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 18 publications
1
22
0
7
Order By: Relevance
“…116,126,148,201 Only six studies provided an adequate description of both the index test and the reference standard. 121,150,155,160,169,183 Eleven studies did not report sufficient information to assess avoidance of test review bias, 116,127,146,148,150,156,157,166,169,201,205 and six did not report sufficient information to assess avoidance of disease progression bias. 116,125,146,155,177,201 The remaining two evaluations of ultrasound techniques used inappropriate reference standard tests of clinical and laboratory diagnosis of APN 211 and computed tomography (CT).…”
Section: Ultrasoundmentioning
confidence: 99%
See 4 more Smart Citations
“…116,126,148,201 Only six studies provided an adequate description of both the index test and the reference standard. 121,150,155,160,169,183 Eleven studies did not report sufficient information to assess avoidance of test review bias, 116,127,146,148,150,156,157,166,169,201,205 and six did not report sufficient information to assess avoidance of disease progression bias. 116,125,146,155,177,201 The remaining two evaluations of ultrasound techniques used inappropriate reference standard tests of clinical and laboratory diagnosis of APN 211 and computed tomography (CT).…”
Section: Ultrasoundmentioning
confidence: 99%
“…All but one of the studies reported that disease progression bias had been avoided. 146 Only two studies provided sufficient details on how MCUG was performed to permit replication, 157,169,183 although all but one provided details on how the reference standard was performed. 157 Two studies reported that the MCUG results were interpreted without knowledge of the reference standard results, and that the reference standard results were interpreted without knowledge of the MCUG results.…”
Section: Mcugmentioning
confidence: 99%
See 3 more Smart Citations